Frugivoria, dispersão de sementes e área de vida por jacutingas (Aburria jacutinga) reintroduzidas na Mata Atlântica - Ferreira, Patricia dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The jacutinga (Aburria jacutinga) is an important seed disperser in the Atlantic Forest that, due to strong hunting pressure, fragmentation and loss of habitat, is threatened with extinction. the vegegetic risks over the years, the program for the Conservation of Gray Birds – Jacutinga Project was created in 2 years, with the aim of reintroducing the species to the Mata00. work monitors hatchlings in captivity and reintroduction of birds in Serra da Mantiqueira, we found that the jacutingas moved from the nursery where they were released, while others remained in the vicinity of the nursery. The home ranges of the jacutingas are the same, ranging from 13.17 ha to 981.92 ha. Regarding the diet, researchers are exploring the environment and experimenting with fruits available in the forest, such as Euterpe edulis, Nectandra megas, Heisteria silviani, so they are fulfilling their seed-dispersing role in similar ways to the species

A jacutinga (Aburria jacutinga) é um importante dispersor de sementes da Mata Atlântica que, devido à forte pressão de caça, fragmentação e perda de hábitat está ameaçada de extinção. Considerando os riscos que esta espécie vem sofrendo ao longo dos anos, foi criado em 2010 o programa para a Conservação das Aves Cinegéticas na Mata Atlântica – Projeto Jacutinga, com o intuito de reintroduzir e monitorar esta espécie na natureza. Neste trabalho acompanhamos aves nascidas em cativeiro e reintroduzidas na Serra da Mantiqueira, constatamos que as jacutingas se deslocaram para longe do viveiro onde foram soltas, enquanto outras permaneceram nas proximidades do viveiro. As áreas de vida das jacutingas acompanhadas variaram de 13,17 ha a 981,92 ha. Em relação a dieta, os indivíduos estão explorando o ambiente e experimentando frutos disponíveis na mata, como Euterpe edulis, Nectandra megapotamica, Heisteria silvianii, portanto estão cumprindo seu papel como dispersora de sementes de forma similar aos indivíduos selvagens da espécie.
Frugivory, seed dispersal and home range of jacutingas (Aburria jacutinga) reintroduced in the Atlantic Forest
Keywords: Endangered birds; Frugivory; Reintroduction; Aves ameaçadas; Frugivoria; Reintrodução